METHODOLOGICAL POSSIBILITIES OF TURNING ENGLISH INTO PRIMARY CLASSES ON THE BASIS OF DIDACTIC MEANS (American Journal of Interdisciplinary Research and Development, 2024)
This article will consider the methodological possibilities of teaching English to primary classes with the integration of didactic tools. The article examines the practical applications of visual weapons, educational games, interactive software, and multimedia resources, relying on theoretical foundations such as constructivism, socio-cultural theories, and communicative language teaching. In addition, it considers pedagogical considerations of moral, cultural and contextual importance in the selection and use of didactic tools.